An analysis of dietary fiber and fecal fiber components including pH in rural Africans with colorectal cancer - Mohammed Faruk; Sani Ibrahim; Ahmed Adamu; Abdulmumini Hassan Rafindadi; Yahaya Ukwenya; Yawale Iliyasu; Abdullahi Adamu; Surajo Mohammed Aminu; Mohammed Sani Shehu; Danladi Amodu Ameh; Abdullahi Mohammed; Saad Aliyu Ahmed; et al. (Intestinal Research, 2018)
Background/AimsColorectal cancer (CRC) is now a major public health problem with heavy morbidity and mortality in rural Africans despite the lingering dietary fiber-rich foodstuffs consumption. Studies have shown that increased intake of dietary fiber which contribute to low fecal pH and also influences the activity of intestinal microbiota, is associated with a lowered risk for CRC. However, whether or not the apparent high dietary fiber consumption by Africans do not longer protects against CRC risk is unknown. This study evaluated dietary fiber intake, fecal fiber components and pH levels in CRC patients.MethodsThirty-five subjects (CRC=21, control=14), mean age 45 years were recruited for the study. A truncated food frequency questionnaire and modified Goering and Van Soest procedures were used.ResultsWe found that all subjects consumed variety of dietary fiber-rich foodstuffs. There is slight preponderance in consumption of dietary fiber by the control group than the CRC patients. We also found a significant difference in the mean fecal neutral detergent fiber, acid detergent fiber, hemicellulose, cellulose and lignin contents from the CRC patients compared to the controls (P<0.05). The CRC patients had significantly more fecal pH level than the matched apparently healthy controls (P=0.017).ConclusionsThe identified differences in the fecal fiber components and stool pH levels between the 2 groups may relate to CRC incidence and mortality in rural Africans. There is crucial need for more hypothesis-driven research with adequate funding on the cumulative preventive role of dietary fiber-rich foodstuffs against colorectal cancer in rural Africans “today.”